Depuis les podiums des reines de beauté : se produire comme femme trans en Bolivie - Pascale Absi (Journal de la Société des Américanistes)
For about ten years now, transgender women’s organizations in Bolivia have been holding beauty pageants. Inspired by the conventional Miss competitions, the aim of these contests is to assert the existence and claim the rights of another category of women. For the participants, these events represent nothing less than a political university; getting up on stage is also a milestone in the journey that leads from hiding to a publicly embraced identity as a trans woman. Nevertheless, the desire to be recognized as equal in beauty and femininity to a Miss limits the possibility of questioning the hegemonic man/woman binary. Thus, in a similar way to the indigenous Miss pageants, the transgender contests seem permeated by the tension between the reproduction of certain means of oppression and a genuinely subversive project.